Pelatihan Pengelolaan Keuangan UMKM Bagi Pengusaha DUIT - Vinola Herawaty; Ayu Oktaviani; Jul Seventa Tarigan; Ati Kushariani (Jurnal Nusantara Mengabdi, 2022)
Purpose: To provide understanding and ability in managing finances to MSME entrepreneurs. Methodology/approach: The method of activity used are (1) counselling and training methods on financial management, where counselling with prepared materials as well as training and direct question and answer sessions during training will be able to make the community able to understand the concept of financial management, (2) assist partners in the process of financial management through good and neat financial records, so that partners can stop excessive spending. The participants for this training are MSME entrepreneurs who are members of Dewan UMKM Indonesia Terpadu (DUIT) Kedoya, West Jakarta. Most of its members are business owners with micro and small-scale businesses. Results/findings: (1) Participants have understood the importance of financial management and are able to manage business finances through good financial records, (2) Participants understand and are able to record financial transactions neatly and according to accounting standards, and (3) Participants have understood and are able to make financial reports as the basis of information for financial management. Conclusion: So far, the income statement is still limited to a report that compares the difference between income and expenses, without separating the nature of the expenditure whether it is an expense or an asset and other accounting provisions that need to be considered by MSME entrepreneurs. Participants need an understanding of the preparation of financial reports in accordance with SAK EMKM, namely income statement, statements of financial position, and notes to financial statements.